PENGARUH SUMBER DAYA MANUSIA DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN DENGAN PEMAHAMAN AKUNTANSI SEBAGAI VARIABEL PEMODERASI - I Nyoman Thegar Suryanatha; Putu Cita Ayu (Hita Akuntansi dan Keuangan, 2021)
Financial reports for MSMEs are accounting information that has an important role to achieve business success, which is the basis of reliable accounting information for economic decision making in managing MSMEs, including market development decisions, pricing and so on so that quality financial reports are needed for MSME. This study has a purfose know the influence of human resource, the use of information technology with the understanding of accounting as a moderating on the quality of financial statements in all of MSME in South Denpasar Subdistrict The population used in this study were all MSMEs in South Denpasar Subdistrict registered with the Office of Cooperatives, Small and Medium Enterprises, as many as 48 MSMEs were active during the Covid-19 pandemic, considering the research carried out during the Covid-19 pandemic period only 16 MSMEs were willing received filling in the questionnaire with 42 respondents, so the sample in this study was 42 people. After testing the instrument and testing the classic assumptions, then the data are analyzed using moderated regression analysis (MRA), determination, t test, and F test. The analysis showed that the effect of human resources on the quality of financial statements with a significance of 0.000 <0.05, so that the first hypothesis (H1) was accepted. The influence of the use of information technology on the quality of financial statements was influenced with a significance of 0.000 <0.05, so that the second hypothesis (H2) was accepted. The influence of accounting understanding to the quality of financial statements with a significance of 0,489 > 0,05, so that the third hypothesis (H3) was rejected. The effect of human resources on the quality of financial statements with the understanding of accounting as a moderating variable with a significance of 0.086 >0.05, so the third hypothesis (H4) was rejected. The influence of the use of information technology on the quality of financial statements with the understanding of accounting as a moderating variable with a significance of 0.014 <0.05, so the fourth hypothesis (H5) was accepted.